2005
DOI: 10.1177/0145721705281563
|View full text |Cite
|
Sign up to set email alerts
|

Use of Continuous Subcutaneous Insulin Infusion (Insulin Pump) Therapy in the Hospital Setting

Abstract: Patients on established insulin pump therapy do not necessarily have to discontinue treatment while hospitalized. However, clear policies and procedures should be established at the institutional level to guide continued use of the technology in the acute care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 7 publications
0
55
0
1
Order By: Relevance
“…14 We sought to protect the patient's desire for autonomy by allowing insulin pump self-management while simultaneously maximizing safety. 13 The formation of a collaborative relationship between the patient and the hospital staff was implied and reinforced by maintaining lines of communication through a daily review of pump operation, surveillance of point-of-care glucose data, and discussion with the patient and staff about any related issues. Since our first publication on this area, others have also presented their approach to inpatient insulin pump management.…”
Section: Introductionmentioning
confidence: 99%
“…14 We sought to protect the patient's desire for autonomy by allowing insulin pump self-management while simultaneously maximizing safety. 13 The formation of a collaborative relationship between the patient and the hospital staff was implied and reinforced by maintaining lines of communication through a daily review of pump operation, surveillance of point-of-care glucose data, and discussion with the patient and staff about any related issues. Since our first publication on this area, others have also presented their approach to inpatient insulin pump management.…”
Section: Introductionmentioning
confidence: 99%
“…At Mayo Clinic, Arizona, patients admitted postoperatively are transitioned to inpatient insulin pump therapy according to established policy. 10 If the patient is discharged home from the PACU, and if the insulin pump was removed during surgery, the patient and the family or caregiver should be instructed to resume insulin pump therapy when the patient is alert and able to operate the device ( Table 2). If insulin pump therapy was continued, the instructions should include contacting the primary diabetes care team for further direction.…”
Section: If the Patient Requires Hospital Admission Pump Therapy Is mentioning
confidence: 99%
“…11 It has been suggested that the policy should assure that there is formal assessment of the patient's competence to manage the pump, that there is professional oversight of the pump management (usually via endocrinology and diabetes educator consultation), that contraindications for CSII use are clearly stated, and that there is a formal mechanism for engaging the patient and informing him of his roles and responsibilities (eg, a written agreement). The clinician must write insulin orders in the medical record that specify the basal and bolus insulin doses which are being used.…”
Section: Continuous Subcutaneous Insulin Infusions (''Insulin Pumps''mentioning
confidence: 99%